2018
DOI: 10.1530/edm-18-0028
|View full text |Cite
|
Sign up to set email alerts
|

Normosmic idiopathic hypogonadotrophic hypogonadism due to a rare KISS1R gene mutation

Abstract: SummaryHypogonadotrophic hypogonadism is due to impaired or reduced gonadotrophin secretion from the pituitary gland. In the absence of any anatomical or functional lesions of the pituitary or hypothalamic gland, the hypogonadotrophic hypogonadism is referred to as idiopathic hypogonadotrophic hypogonadism (IHH). We present a case of a young lady born to consanguineous parents who was found to have IHH due to a rare gene mutation.Learning points:The genetic basis of a majority of cases of IHH remains unknown.I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…Males can be clinically manifested as absent or incomplete puberty, small penis, cryptorchidism, and infertility. 12 In the past few years, IHH has classically been categorized as a single-gene disease, 13 but the phenotypic presentation of this disease and its genetic background are highly heterogeneous. 14 A few genes that are involved in the pathogenesis of IHH have been identified at various sites, including TAC3, TACR3, GnRHR, FGFR1, GNRH1, FGF8, KISS1, and KISS1R.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Males can be clinically manifested as absent or incomplete puberty, small penis, cryptorchidism, and infertility. 12 In the past few years, IHH has classically been categorized as a single-gene disease, 13 but the phenotypic presentation of this disease and its genetic background are highly heterogeneous. 14 A few genes that are involved in the pathogenesis of IHH have been identified at various sites, including TAC3, TACR3, GnRHR, FGFR1, GNRH1, FGF8, KISS1, and KISS1R.…”
Section: Discussionmentioning
confidence: 99%
“…16 Mutations of this gene have been identified in less than 5% of patients with normosmic IHH. 12 Up to now, at least 20 different mutations have been described in the literature, most of which were loss-of-function mutations and were found to have variable clinical manifestation. 12 20 These studies indicated that heterozygous mutations in KISS1R could be also involved in the pathogenesis of IHH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Idiopathic hypogonadotropic hypogonadism with normal sense of smell (normosmic IHH) or with hypoosmia or anosmia (Kallman syndrome) is a complex and rare disorder characterised by insufficient GNRH neuronal action on an otherwise normal hypothalamo-pituitarygonadal axis. This could be due to defective development or migration of GNRH neurones, impaired secretion of GNRH from neurons, disrupted interaction between the GNRH ligand and its receptor, or impaired secretion of LH and FSH (2,3). To date, pathogenic variants in around 50 genes have been reported to cause IHH which account for up to 50% of IHH cases, suggesting that further genes remain to be discovered (4).…”
Section: Introductionmentioning
confidence: 99%
“…Kiss1-GPR54 signaling is fundamental to GnRH-driven fertility (Leon et al, 2016). Mutation in Kp or in GPR54 are the main reasons for various types of reproductive axis disabilities such as, iodiopathic hypogonadotropic hypogonadism (Kotani et al, 2014), central precocious puberty (Oh et al, 2017) and Normosmic idiopathic hypogonadotrophic hypogonadism (Chelaghma et al, 2018).…”
Section: Introductionmentioning
confidence: 99%